PENGEMBANGAN MODUL CONTEXTUAL TEACHING AND LEARNING (CTL) BERORIENTASI GREEN CHEMISTRY UNTUK PERTUMBUHAN LITERASI SAINS SISWA - Hari Prima Ahmadi; Suryati Suryati; Yusran Khery (Hydrogen: Jurnal Kependidikan Kimia, 2016)
Acid-base is one of topics considered difficult by students. This concept is broad,  varied. Despite it is very closely related to everyday life, its application was still lacking. The development of teaching materials in the form of a module was deemed to be a solution to this problem. The aim of this research was to develop CTL module with green chemistry orientation in acid-base subject material to improve science literacy of students. This study was developed ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The developed product was validated by three experts, a practitioner and ten high school students. Data were analyzed using percentage formula. Qualitative data in the form of comments and suggestions from validator were used as consideration to revise the developed module.Tthe effectivity of the module was assessed using N-gain test. Based on validation results, we obtained average of 86,5%, 97%, 88%, and 94,58%. Effectivity evaluation using N-gain test shows an average score of 0,5 with moderate category. Result of student attitudes towards science data has an average score of 74% with good qualifications. It was concluded that developed module prototype is effective for acid-base topic, and most likely for other topics in learning process and growing student science literacy.